Complications of dexamethasone implants: risk factors, prevention, and clinical management - Celik, Nil; Khoramnia, Ramin; Auffarth, Gerd U.; Sel, Saadettin; Mayer, Christian (International journal of ophthalmology, 2020)
AIM: To evaluate major complications after intravitreal injection of dexamethasone implants (Ozurdex) and their clinical management. METHODS: In a retrospective observational study between 2014 and 2016 at two university hospitals, we reviewed the clinical records of 1241 consecutive macular edema patients treated with the dexamethasone implant, and separated severe adverse events in the injection procedure from those that were post-injection complications. We evaluated the cause and the outcomes in each case. RESULTS: In twenty-one procedures (1.69%) we noticed significant complications during and after intravitreal injection of the dexamethasone implant. Complications related to the injection procedure were in one case, that a second implant was injected by mistake in the same eye on the same day. In another case, the implant lodged in the sclera during retraction of the injector needle. Leaking scleral tunnel at the injection site led to hypotony in another case. There were 10 cases of post-injection displacement of the implant into the anterior chamber and one case with a migrated and trapped device between the intraocular lens and an artificial iris. Displacement typically occurred in patients with preexisting risk factors: eyes with complicated intraocular lens implantation, iris reconstruction or iris defects or pseudophakic eyes after vitrectomy were prone to develop this complication. Displacement led to secondary corneal decompensation with pseudohypopyon. One case developed an endophthalmitis, and we observed four cases of retinal detachment. Two eyes presented with long-lasting hypotony due to ciliary insufficiency. CONCLUSION: Treatment with the dexamethasone implant may cause various expected or unexpected complications that may have serious consequences for the patient and require further surgery. To reduce complications, clinicians should evaluate certain risk factors before scheduling patients for dexamethasone implant treatment and use proper injection techniques.
Gesehen am 05.11.2020